(untitled) (Research, Society and Development, 2021)
The temporomadibular joint (TMJ) is considered one of the most complex joints in the human body. It is involved in multipl functions, including chewing and phonation. It is considered na extremely adaptative structure. It is involved in multiple functions, including several pathologies can affect the TMJ and result in dysfunctions that significantly interfere in patients’ lives. Temporomandibular disorders (TMD) are associated with a large number of etiologies. Animal experimental models represent a possibility for the anatomical, histological and physiological study of this structure, the induction of dysfunctions and establishment of treatments. The aim of this literature review is to present and discuss the use of animal models for the study of TMJ. The literature review was carried out through a literature search in the Pubmed (https://pubmed.ncbi.nlm.nih.gov/), Scielo (scielo.org) and Bireme (http://bvsalud.org) databases. According to the literature review, so far, no animal model is totally similar to the human TMJ. This characteristic represents a limiting factor in the investigation of possible surgical and non-surgical therapies for TMDs. Since there is no single model, researchers must choose the animal model that most applies to the objective of the study to be carried out.